Processing Documents and Business Legality and Promoting Takoyaki Yoi Batam Products - Fendi Cuandra; Meirita Sita Dewi (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Takoyaki Yoi Batam is one of the Micro, Small, Mediun, Enterprises in Batam City that sells takoyaki. Takoyaki is food from Japan. Takoyaki Yoi Batam is located at SP Plaza Square Outlet, SP Ruko Complex, Jl Letjen R. Suprapto, Tembesi, Kec. Sagulung, Batam City. The place of business is a small stand. Takoyaki Yoi Batam does not yet have a Business Identification Number as a form of business legality document. In addition, Takoyaki Yoi Batam also lacks customer engagement on Instagram. Therefore, in this community service plan the Takoyaki Yoi Batam business on the OSS (Online Single Submission) website to create a Business Identification Number and increase customer engagement on Instagram to increase brand awareness, loyalty, and takoyaki sales, and establish good relations with consumers. The purpose of this community service is to assist micro, small and medium enterprises to create a Business Identification Number and increase customer involvement and sales. The research methodology used is a qualitative research method. Data collection by means of interviews, observation, and documentation. Primary data comes from interviews with Takoyaki Yoi Batam business owners. The result of this community service is that Takoyaki Yoi Batam has a Business Identification Number and uses Instagram as a marketing tool to increase customer engagement and sales.